A One‐Pot Chemically Cleavable Bis‐Linker Tether Strategy for the Synthesis of Heterodimeric Peptides. Issue 47 (16th August 2016) - Patil, Nitin A.; Tailhades, Julien; Karas, John A.; Separovic, Frances; Wade, John D.; Hossain, Mohammed Akhter
Abstract: Heterodimeric peptides linked by disulfide bonds are attractive drug targets. However, their chemical assembly can be tedious, time‐consuming, and low yielding. Inspired by the cellular synthesis of pro‐insulin in which the two constituent peptide chains are expressed as a single‐chain precursor separated by a connecting C‐peptide, we have developed a novel chemically cleavable bis‐linker tether which allows the convenient assembly of two peptide chains as a single "pro"‐peptide on the same solid support. Following the peptide cleavage and post‐synthetic modifications, this bis‐linker tether can be removed in one‐step by chemical means. This method was used to synthesize a drug delivery‐cargo conjugate, TAT‐PKCi peptide, and a two‐disulfide bridged heterodimeric peptide, thionin (7‐19)‐(24‐32R), a thionin analogue. To our knowledge, this is the first report of a one‐pot chemically cleavable bis‐linker strategy for the facile synthesis of cross‐bridged two‐chain peptides. Abstract : Tethered together : A dimedone‐based N‐terminal linker was developed for use in a bis‐linker tether strategy for efficient synthesis of heterodimeric peptides. Sequential solid‐phase synthesis of two peptide chains on the same solid support, separated by the tether, followed by their folding and chemical cleavage of the bis‐linker tether yielded the heterodimeric peptide.